APPLICATION OF BASEL II TREATMENT TO THE RISK MANAGEMENT SYSTEM OF THE BANKS IN THE SYSTEM VIETINBANK DONG NAI - Tram, Đỗ Thị Thanh; Thu, Trần Thị Anh (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2022)
This study is intended to discuss risk management and its importance to the fundamental operations of Vietinbank in Dong Nai, and whether the Basel II Accords have any significance to the severity. recession by creating capital shortages at banks at Vietinbank in Dong Nai and in general. The questionnaire was answered by key risk managers in branches of Vietin Dong Nai bank. The questions consist of three main parts with a total of 42 questions. The first part: 12 questions and focuses on the assessments obtained about the importance and effectiveness of the 5 key risk management techniques. The second part : 28 questions and was used to answer 4 questions: the level of understanding and implementation of risk management, the most effective tools and techniques banks are using to manage risk, open to managers who are aware of risks related to operations and objectives, and the Basel II Agreement supports or hinders risk management among banks in Vietinbank. It is based on a Likert scale (5 levels) for each individual indicator. Part three: two qualitative open-ended questions designed to obtain subjective information about their specific understanding of risk and risk management, as well as clarify answers to the quantitative questions. Based on the analysis results in this study, the author draws conclusions and proposes solutions for the research object which are banks in the Vietinbank Dong Nai banking system